Hierarki kebutuhan abraham maslow sebagai solusi problematika mufrodat dalam pemerolehan bahasa arab di pondok modern darul-ihsan nganjuk - Luqman, Muhammad Luthfi (Maliki Interdisciplinary Journal, 2026)
This study discusses the problematics of Arabic vocabulary (mufrodat) acquisition among santri at Pondok Modern Darul-Ihsan Nganjuk through the perspective of Abraham Maslow’s Hierarchy of Needs theory. The research aims to identify the forms of difficulties experienced by santri in mastering mufrodat and to analyze how the fulfillment of psychological needs contributes to more effective language acquisition. This study employed a qualitative approach using a case study design. Data were collected through classroom and dormitory observations as well as semi-structured interviews with santri and Arabic language teachers. The findings reveal that santri’s difficulties in mastering mufrodat are not merely caused by linguistic or cognitive limitations, but are strongly influenced by affective factors, particularly unmet needs for safety, belonging, and esteem. Feelings of anxiety, fear of making mistakes, and concern over negative social responses hinder santri from actively using the vocabulary they have learned. The study demonstrates that fulfilling these basic psychological needs creates a more supportive learning environment, encouraging confidence and active language use. The findings contribute to the field of Arabic language acquisition (Iktisābul Lughah) by highlighting the relevance of humanistic psychology in vocabulary acquisition and offering practical implications for developing more humane and psychologically supportive Arabic learning environments in Islamic boarding schools.